Effect of intraperitoneal docetaxel on ovarian function in mice. (17th November 2022) - Yoshida, Kanako; Erdenebayar, Otgontsetseg; Kadota, Yuri; Kasai, Kana; Kawakita, Takako; Shinya, Akari; Sasasda, Hikari; Katayama, Sachiko; Nii, Mari; Imaizumi, Junki; Kamada, Shuuhei; Kagawa, Tomohiro; et al.
Abstract: Taxanes are important chemotherapeutic agents used to manage breast cancer and gynaecological malignancies. However, ovarian toxicity induced by the taxane docetaxel (DOC) is of great concern. We investigated DOC-induced toxicity in the ovaries of female CD1 strain mice. The mice were divided into control (saline), DOC-5 (5 mg/kg DOC), and DOC-10 (10 mg/kg DOC) groups and administered saline or DOC on the first day of the study and two weeks later. Two weeks after the second dose, the ovaries were removed for analysis after inducing superovulation. Ovary weight, the number of secondary follicles, and the total number of follicles were reduced after DOC administration. Additionally, the expression levels of caspase-3 and the pro-apoptotic protein Bcl-2 interacting mediator of cell death (BIM) increased. Our findings suggest that high-dose DOC induces damage to growing follicles; however, it may not affect primordial follicles. Impact statement: What is already known on this subject? Docetaxel (DOC) is one of the most effective chemotherapeutic agents used to manage various cancers. Some in-vitro studies have examined paclitaxel-induced ovarian toxicity; however, limited research on DOC is available. What do the results of this study add? We investigated DOC-induced ovarian toxicity in female CD1 strain mice at 5 mg/kg and 10 mg/kg. We found that DOC reduced ovary weight, the number of secondary follicles, and the total number of follicles, with the higher dose having a higher effect. What are the implications of these findings for clinical practice and/or further research? We believe that our study makes a significant contribution to the knowledge about the effect of DOC on ovarian function.